Pengaruh Temperatur dan Rapat Arus Terhadap Kekerasan dan Distorsi Kisi pada Hard Chromium Plating pada Baja Karbon Rendah - Riska Rachmantyo; Aditianto Ramelan; Akhmad Zein Eko Mustofa; Asep Ridwan Setiawan (Jurnal Metalurgi dan Material Indonesia, 2019)
Hard Chromium Plating is one of several coating techniques that has been applied to engineering components. The hard chromium layers have several properties such as, hardness, high corrosion and wear resistance. In fact the quality is determined by several process parameters during electro deposition. In this experiment temperature and current density were varied to observe the effect on the quality of hard chromium layer deposited on a steel base plate. This was to find the appropriate combination of producing deposited layer with the optimum quality. The electroplating process was carried out for 60 minutes at 50, 55 and 60 oC with current density variation of 70, 80 and 90 A/dm2. The specimen were then undergone hardness test and XRD characterization. Maximum hardness measured was 1128 HV this was plated at 55°C with a current density of 80 A/dm2. XRD analysis shown that the increasing hardness of hard chromium plating is related with an increase of microstrain calculated from the diffractogram pattern.